Diversity of the selected elements of agricultural potential in the European Union countries - Agnieszka Tłuczak (Agricultural Economics (AGRICECON), 2020)
Agricultural importance in determining the directions of respective regions results from its production potential. The agricultural potential of a given country is determined by natural resources, ways of using them, natural conditions, workforce resources, technical resources and basic economic conditions. In this paper, only income and rural population are taken under consideration to describe the agricultural potential. Currently, European Union countries are functioning under the assumptions of the Common Agricultural Policy, assuming, among other things, increasing agricultural productivity, ensuring an adequate standard of living for the rural population and stabilising markets. The European Union (EU) is one of the world's leading exporters and importers of agricultural products. The obtained results allowed the identification in 2010 and 2018 of countries with high and low values of income and population potential. It is characteristic that within both potentials, population and income, the countries with the lowest potentials are the most numerous group. Poland and Romania stand out against the background of all countries, where due to the high share of people working in agriculture, the population's potential has the highest values. Denmark is also an outstanding country for which income potential has the highest value. This study aims to examine the diversity of selected elements of agricultural potential in the European Union countries. The research was conducted using, among other potential models and global and local spatial autocorrelation statistics. The analysis covered the years 2010 and 2018 by applying statistical data (Eurostat, Statistical Yearbook of Agriculture).